2006
DOI: 10.1007/bf02763052
|View full text |Cite
|
Sign up to set email alerts
|

Congenital CMV infection in symptomatic infants in Delhi and surrounding areas

Abstract: Many viral infections are associated with significant maternal and fetal consequences during pregnancy among which cytomegalovirus is one of the most important agent, globally. Both primary and recurrent infection due to this virus can result in fetal infection. Samples from Congenital Anoammaled babies are referred to NICD from Delhi based Government hospitals and surrounding areas for diagnosis of congenital infections like Toxoplasm, Rubella, CMV and Herpes. In the present study, accumulated data is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 12 publications
2
23
2
Order By: Relevance
“…Serological surveys in different parts of India have shown 80-90 % prevalence of CMV IgG antibodies in women of childbearing age [48]. In the present study, 92 % of HRP women were positive for IgG only, indicating remote infection while 5 % were positive for both IgG ?…”
Section: Discussionsupporting
confidence: 44%
“…Serological surveys in different parts of India have shown 80-90 % prevalence of CMV IgG antibodies in women of childbearing age [48]. In the present study, 92 % of HRP women were positive for IgG only, indicating remote infection while 5 % were positive for both IgG ?…”
Section: Discussionsupporting
confidence: 44%
“…A few studies have shown the high prevalence of CMV as the etiological agent in babies born with birth defects. [6][7][8] The rapid and correct diagnosis of congenital CMV congEnItal cmv InfEctIon; dIagnosIs In sYmPtomatIc Infants…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, IgG -low avidity antibodies together with reactive CMV IgM strongly support the diagnosis of maternal primary infection in the preceding 3 or 4 months 26,27 . India has higher seroconversion rate (2%-2.5%) among pregnant population, whereas only one sample (0.25%) showed low affinity antibodies indicating primary infection 19,20 . Equivocal results were found in 2.75% of IgG positive samples.…”
Section: Discussionmentioning
confidence: 93%
“…Seropositivity rates lie between 50%-60% in developed countries, and the rates are between 90%-100% in developing countries 19,20 . CMV seropositivity rates are higher in women of reproductive age especially in low socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation